A study on the awareness of Malaysia's manufacturing industries in implementing industry 4.0 - Mohd Hamka, Nurhazimah (2017)
Today, there are many challenges faced by the manufacturing sector with respect to the disruptive concepts like Cyber-Physical Systems, Internet of Things, Cloud-based Manufacturing, which is also known as the Industry 4.0. The concept of Industry 4.0 was first introduced at Hannover Fair (Germany) and it was seen to be a high-tech approach, which would lead to an intelligent manufacturing. The main aim of Industry 4.0 is improving the existing processes and products by using modern digital technologies and providing more opportunities for developing novel business models. Currently, the manufacturing sector ought to alter their policies and adapt the trending transformations if they wish to face their competitors. Several companies have begun investing in the essential Industry 4.0 resources because they faced a steady decline in their productivity levels when using conventional techniques. In this study, the researchers have aimed to investigate the Industry 4.0 implementation and determine the awareness levels of the Malaysian manufacturing industries with regards to this concept. The researchers have investigated all the different sectors in the Malaysian manufacturing companies, whether they are Small and Medium-scale Enterprises (SMEs), Government Link Companies (GLCs) or national and multinational corporations. In this study, the researchers used a survey-based research technique, where they used a sample size of 91 Malaysian manufacturing industries. The researchers carried out the survey amongst the employees and the managers, who represented their company. Few questionnaires were prepared and circulated amongst all the companies between May and June 2017. More than 50 of the Malaysian manufacturing industries completed the questionnaires and participated in the personal interviews. All results obtained after the survey were analysed using the Descriptive Statistic Analysis. Based on the results, it could be seen that 50.5% of the respondents were familiar and aware of the Industry 4.0, while 49.5% were unfamiliar with the concept. Furthermore, the results showed that the familiarity and the awareness of the Industry 4.0 amongst the managers was dependent and was influenced by their foreign-owned company type and sector as the multinational companies possessed a higher amount of advanced assets which led to a higher production. An additional 6 factors like data-driven services, smart operation, smart factory, smart product, employees and the strategy and organisation also contributed to the company’s digital transformation, which was further benefitted by various exponential technologies. The findings of this study were very useful for future research as they helped in establishing a future model framework for the assimilation of the Industry 4.0 concept amongst the Malaysian manufacturing industries.